Managing Fertilizer Recommendations in Rice-Based Cropping Systems Challenges and Strategic Approaches - Bado, V.B.; Djaman, K.; Valère, M.C. (Springer, 2018)
Improving agricultural productivity to facing the fast growing food demands is the huge challenge of Sub-Saharan Africa (SSA). Fertilizer is a powerful productivity-enhancing input, but farmers of SSA use only 5 to 9 kg ha−1 of fertilizer, ten time less than Latin America and Asia (50 and 80 kg ha−1, respectively). Rice (Oryza sativa) is one of the most important food crops of SSA and rice consumption is growing faster than the consumption of any other commodity in Africa. Rice-based systems have high potential for improving food production through an efficient management of fertilizers. The biophysical environment, cropping systems and, socio-economic environment of farmers including market opportunities are the main factors for development of appropriate fertilizer recommendations. This paper makes a critical review of rice-based systems in Africa and the main achievements on fertilizer recommendation, and further identifies the main challenges and opportunities to improve fertilizer use efficiency in rice-based systems. The opportunities offered by the new concepts, modeling and decision support tools that have been recently developed for better management of fertilizers in rice systems have been discussed. Beyond the traditional techniques of blanket fertilizer recommendations by country, some suggestions are proposed to improve the utilization of the new concepts and decisions support tools for better management of fertilizer in the rice-based systems.